2000
DOI: 10.1080/j.1440-1614.2000.00761.x
|View full text |Cite
|
Sign up to set email alerts
|

Public Beliefs About the Helpfulness of Interventions for Depression: Effects on Actions Taken When Experiencing Anxiety and Depression Symptoms

Abstract: Beliefs about the helpfulness of an intervention did not always predict actual use of that intervention, although beliefs did predict use of antidepressants. Therefore, campaigns that change public beliefs about effective treatments may also influence actual use of treatments. Interventions preferred by professionals are not frequently used at present. Most people with anxiety and depression symptoms rely primarily on simple self-help interventions, the effectiveness of which has been little researched.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
111
4
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(128 citation statements)
references
References 17 publications
11
111
4
2
Order By: Relevance
“…Jorm et al (2000) have found accumulating evidence for the link between better mental health literacy and more positive attitudes to seeking professional help and service use. So far, mental health literacy has been measured as objective knowledge of mental health-related facts.…”
Section: Introductionmentioning
confidence: 99%
“…Jorm et al (2000) have found accumulating evidence for the link between better mental health literacy and more positive attitudes to seeking professional help and service use. So far, mental health literacy has been measured as objective knowledge of mental health-related facts.…”
Section: Introductionmentioning
confidence: 99%
“…The finding that depressed patients strongly prefer psychotherapy compared to medication, which was even more accentuated in the subgroup of previously depressed and currently nondepressed patients, is supported by previous studies. 6,7,[12][13][14][15][16][17] Our result, that depressed patients frequently attribute improved well-being to psychotherapy, but rarely to antidepressant medication, might partially explain the preference for psychotherapy. Other study results indicate that this preference might go back to the patients' belief that emotional problems are most frequently caused by alterable factors, such as interpersonal problems, work-related problems, and health problems.…”
Section: Discussionmentioning
confidence: 99%
“…Within the subgroup of previously depressed and currently nondepressed patients, 31% preferred psychotherapy and 0% antidepressant medication (w 2 =11.9, Po.001). anxiety, worries, depression, lack of self-confidence 12 (14) 8 (9) Non-satisfactory medical care 9 (10) 3 (3) Nothing/don't know z‰ 7 (8) 28 ( Ã Assessed with open-ended question: ''Was there something that impaired your emotional well-being? ''…”
Section: Preference For Psychotherapy or Antidepressant Medication Inmentioning
confidence: 99%
See 2 more Smart Citations